ENGLISH TEACHING FOR SPECIFIC PURPOSE AT A HIGHER ENGINEERING INSTITUTION: TEACHING MODEL OF SPOKEN LANGUAGE - Podorozhna , A. (Problems of Engineer-Pedagogical Education, 2021)
The characteristics of the foreign language professional-oriented training of future engineer-teachers are defined in this article. Contemporary approach of English teaching for specific purpose involves the development of foreign language communicative skills of students in certain professional, business, scientific spheres and situations according to the characteristics of professional thinking, when organizing incentive-motivational and targetresearch activity. This is indeed a fundamental departure from language teaching for general educational purposes and socialization in education processes. However, English teaching for specific purpose of engineering students at higher school is not limited to learning «language for specific purpose». There are some certain features common to specific to the different contexts of language use, which students are likely to face in real communicative situations. However, it was necessary to take into consideration that functional lexis and grammar proficiency cannot sufficiently compensate for the lack of knowledge and skills, to enable implementation of activities that is insufficient development of communicative competence. The difficulties of the foreign language professional-oriented training in engineering and pedagogical higher educational establishments are considered and the methods of their resolving are proposed in this article The model of foreign-language oral speech teaching concerning to the specialty is offered, the examples of exercises, directed to the speech skills and abilities development, and the abilities forming of creative reconsideration of the text are given. Based on what the main goal of English teaching for special purpose is to develop not only speech, but also professional-communicative skills, the exercises on the development, training and firmly establishing foreign language skills and abilities have to be situational, information-intensive, and time-consuming, create the conditions for foreign language communication in the professional context. Various types of exercises can be put in place in the process of English teaching for special purpose of engineering students, what entails the potential for creative potential of a teacher as well as students. According to the article, the essence of English teaching for specific purpose of engineering students is to integrate it with special disciplines in order to gain additional professional knowledge and to develop such personal qualities, necessary for future vocational activity, to develop communicative skills of students, to help them realize professional contacts in English in various fields and situations; with the aim of optimizing professional-oriented training and successful development of communicative-projecting skills it is necessary to develop and apply new training modules on specialty, providing the realization of professional-oriented foreign language training and motivation encouragement of engineering students at higher education institution.